Cover Picture: An [Fe‐Fe]‐Hydrogenase Mimic Immobilized on MCM‐41 for the Photochemical Production of Hydrogen in Pure Water (Chin. J. Chem. 6/2014). Issue 6 (June 2014) - Wang, Wen; Yu, Tianjun; Zeng, Yi; Chen, Jinping; Li, Yi
<x xml:space="preserve">Abstract</x> The cover picture shows a convenient approach for the application of water‐insoluble hydrogenase mimics in water. A hydrophobic hydrogenase mimic has been successfully applied to the photochemical production of hydrogen in pure water by immobilization of it into MCM‐41 with an iridium compound [Ir(ppy)2bpy]Cl and triethylamine as the photosensitizer and the sacrificial electron donor, respectively. The immobilization stabilizes hydrogenase mimic, which endows the catalytic system good catalytic activity. The present study provides a general strategy for applying hydrophobic artificial catalysts in pure water by using mesoporous molecular. More details are discussed in the article by Li et al. on page 479–484.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>